Estudio de la inestabilidad del sistema eléctrico de potencia del campo petrolero pindo de la ciudad de Puerto Francisco de Orellana durante el año 2015. diseño del sistema de coordinación de protecciones eléctricas - Estrella Cevallos, Ricardo Santiago (2016)
This research was performed with the aim of designing a system of electrical protection coordination toavoid that generating units disconnect automatically of the system in front of failures in the distributionnetwork, determining that technically and economically is justified making modifications, both thedistribution and protection to eliminate the susceptibility of the electrical system isolated by faults thatmay be limited to one part of the distribution network in the oilfield Pindo. At the beginning, itdevelops all the theoretical elements necessary for a training assimilation of the current problems andcreates the necessary basis for its solution, the effects of the low stability of the powerful systemstandards for the control and reduction are discussed, including the main lawsand rules to control andreduce all of these. Next, a detailed description of the system under analysis, its component parts andpowerful system is performed, a detailed analysis of the problems encountered are also made, as wellas the methodology for evaluation. It also includes all measurements in order to perform simulationsand adopt the most appropriate variants to ensure a stable electrical powerful system.